Vejrforholdene i Landbrugsaaret 1384—85o: fra 1ste Oktbr. 1884 til 30te Septbr. 1885. - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1384—85o: fra 1ste Oktbr. 1884 til 30te Septbr. 1885.